T-Cell Metabolism in Graft Versus Host Disease - Karl, Franziska; Hudecek, Michael; Berberich-Siebelt, Friederike; Mackensen, Andreas; Mougiakakos, Dimitrios (Frontiers in Immunology, 2021)
Allogeneic-hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for numerous hematological malignancies. Elimination of malignant cells depends on the T-cells’ Graft-versus-Tumor (GvT) effect. However, Graft-versus-Host-Disease (GvHD), often co-occurring with GvT, remains an obstacle for therapeutic efficacy. Hence, approaches, which selectively alleviate GvHD without compromising GvT activity, are needed. As already explored for autoimmune and inflammatory disorders, immuno-metabolic interventions pose a promising option to address this unmet challenge. Being embedded in a complex regulatory framework, immunological and metabolic pathways are closely intertwined, which is demonstrated by metabolic reprograming of T-cells upon activation or differentiation. In this review, current knowledge on the immuno-metabolic signature of GvHD-driving T-cells is summarized and approaches to metabolically interfere are outlined. Furthermore, we address the metabolic impact of standard medications for GvHD treatment and prophylaxis, which in conjunction with the immuno-metabolic profile of alloreactive T-cells could allow more targeted intervention in the future.